Medieval music - Hoppin, Richard H. (New York W.W. Norton & Company, 1978)
The present book will be of great usefulness to the college student who wants more information than can be gleaned from a survey of all Western music but may not have time for an intensive study of the entire medieval repertory.The book will prove interesting and helpful to the increasing number of amateurs who, through both live and recorded performances, have come to know and love the strangely beguiling qualities of medieval music. Perhaps, in addition, it may contribute to a wider realization that the Middle Ages produced music worthy of the same careful study and admiration long accorded to its masterpieces of literature, art, and architecture.